Model of Competitive Advantage in The Food And Beverage Sector in West Bandung District - Yun, Yun; Primiana, Ina; Kaltum, Umi; Sarasi, Vita (Indonesian Journal of Sustainability Accounting and Management, 2025)
This study examines the role of supply chain partnerships and information sharing in enhancing competitive advantage, with supply chain integration serving as a mediating construct, specifically within micro and small food and beverage enterprises in West Bandung Regency, Indonesia. The research provides novelty through its focus on a rarely explored sectoral context and the application of Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess complex inter-variable relationships. A quantitative research design was employed, involving 125 food and beverage business actors selected using a stratified simple random sampling method. Respondents met the criteria of having operated for more than three years and generating annual revenue below IDR 500 million. Data were collected through structured questionnaires and analyzed using PLS-SEM to test both the measurement and structural models. The findings reveal that both supply chain partnerships and information sharing have a significant positive influence on competitive advantage when mediated by effective supply chain integration. These results emphasize the strategic value of integrated networks in achieving sustainable market positioning. The study concludes that MSMEs in the food and beverage sector must prioritize integrated supply chain development to enhance collaboration and improve responsiveness, thereby strengthening their overall competitive advantage.